The end of the ages has come an early interpretation of the passion and resurrection of Jesus - Allison, Dale C. (Edinburgh, Scotland T and T Clark, 1987)
Includes bibliographical references and index.
Keywords: JESUS CHRIST - DEATH AND RESURRECTION; Jesus Christ -- crucifixion -- biblical teaching; Jesus Christ -- resurrection -- biblical teaching